Type B lamins remain associated with the integral nuclear envelope protein p58 during mitosis: implications for nuclear reassembly. - Meier, J (1994)
p58 (also referred to as the lamin B receptor) is an integral membrane protein of the nuclear envelope known to form a multimeric complex with the lamins and other nuclear proteins during interphase. To examine the fate of this complex during mitosis, we have investigated the partitioning and the molecular interactions of p58 in dividing chicken hepatoma (DU249) cells. Using confocal microscopy and double immunolabelling, we show here that lamins B1 and B2 co-localize with p58 during all phases of mitosis and co-assemble around reforming nuclei. A close juxtaposition of p58/lamin B-containing vesicles and chromosomes is already detectable in metaphase; however, p58 and lamin reassembly proceeds slowly and is completed in late telophase--G1. Flotation of mitotic membranes in sucrose density gradients and analysis of mitotic vesicles by immunoelectron microscopy confirms that p58 and most of the type B lamins reside in the same compartment. Co-immunoprecipitation of both proteins by affinity-purified anti-p58 antibodies shows that they are physically associated in the context of a mitotic p58 'sub-complex'. This sub-assembly does not include the type A lamins which are fully solubilized during mitosis. Our data provide direct, in vivo and in vitro evidence that the majority of type B lamins remain connected to nuclear membrane 'receptors' during mitosis. The implications of these findings in nuclear envelope reassembly are discussed below.